Eating behaviors and health-related quality of life: A scoping review. (November 2022) - Pano, Octavio; Gamba, Magda; Bullón-Vela, Vanessa; Aguilera-Buenosvinos, Inmaculada; Roa-Díaz, Zayne M.; Minder, Beatrice; Kopp-Heim, Doris; Laine, Jessica E.; Martínez-González, Miguel Ángel; Martinez, Alfredo; Sayón-Orea, Carmen
Highlights: Appropriate lifestyles improve the well-being of people with non-communicable diseases. Diet is a key aspect of lifestyle that results from social, cultural, and regional differences. Targeting eating behaviors in patients with chronic disease can significantly improve health-related quality of life. Research has overlooked particular eating behaviors, to the detriment of health-related quality of life. Abstract: Discrepancies between total life expectancy and healthy life expectancy are in part due to unhealthy lifestyles, in which diet plays an important role. Despite this knowledge, observational studies and randomized trials have yet to show consistent improvements in health and well-being, also known as health-related quality of life (HRQoL), given the variety of elements that conform a healthy diet aside from its content. As such, we aimed to describe the evidence and common topics concerning the effects of modifiable eating behaviors and HRQoL in patients with non-communicable diseases (NCD). This scoping review of six electronic databases included 174 reports (69 % were experimental studies, 10 % longitudinal studies, and 21 % cross-sectional studies). Using VOSviewer, a bibliometric tool with text mining functionalities, we identified relevant aspects of dietary assessments and interventions. Commonly observed topics in experimental studies were those related to diet quality (micro- and macronutrients, food items, and dietary patterns). In contrast, less was found regarding eating schedules, eating locations, culturally accepted food items, and the role of food insecurity in HRQoL. Disregarding these aspects of diets may be limiting the full potential of nutrition as a key element of health and well-being in order to ensure lengthy and fulfilling lives.